Decellularized Matrix Scaffolds for Vascular Transplantation: Addressing Immunogenicity, Sterilization, and Current Strategies for Long-Term Storage - Yevhen V. Shevchenko; Tetiana I. Liadova; Fedir V. Hladkykh; Mariia S. Matvieienko; Mykola O. Chyzh; Roman R. Komorovsky (Український журнал серцево-судинної хірургії)
Cardiovascular diseases are the leading cause of death globally, with their incidence rising rapidly. For obstructive cardiovascular diseases, definitive treatment options include surgical interventions such as vascular stenting, replacement surgery, or vascular bypass. Decellularized extracellular matrix scaffolds, designed through tissue engineering, hold great potential in addressing the donor shortage issue.